THE HOUSE OF MOHAMED SHARIF IN AL-FAHIDI NEIGHBORHOOD, A MODEL OF TRADITIONAL HOUSES IN DUBAI - UNITED ARAB EMIRATES - Laila Mahmoud Hassan Tony (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2022)
This study sheds light on the architectural and urban character of traditional houses in the Emirate of Dubai in the United Arab Emirates, and its plastic and formative qualities during the civilizational stages before the construction boom in the second half of the twentieth century. In addition to knowing the types and models of architectural planning, and that architectural planning in Dubai is the same planning that was prevalent in the rest of the Arabian Gulf region. The main objective of this study is to shed light on the traditional architecture in Dubai and to know the architectural and decorative elements by combining the descriptive and analytical method, for a model of these houses in the Al Fahidi "Al Bastakiya" area, which is the house of Mohamed Sharif Sultan Al ‘‘Ulama